A Diversity in Clinical and Neurophysiological Manifestations of Epilepsy with Eyelid Myoclonia (Jeavons Syndrome) in Pediatric Population - Mohammadi , Mahmoud; Shervin Badv, Reza; Zamani, GholamReza; Beiraghi Toosi, Mehran; Heidari, Morteza; Rezaei, Zahra; Eslamiyeh, Hossein (Iranian Journal of Child Neurology, 2025)
Objectives: Epilepsy with eyelid myoclonia (EEM), with or without absence, also known as Jeavons Syndrome (JS), is a unique epileptic syndrome. This syndrome may be accompanied by other generalized seizures, such as generalized, tonic-clonic, myoclonic, and rarely atomic seizures. This study was conducted to determine the diversity of clinical and neurophysiological manifestations of JS in the pediatric population of Iran. Materials & Methods: This retrospective, cross-sectional study was conducted at the Children’s Medical Center of Tehran, Iran, from 2017 to 2023. Two clinical neurophysiologists reviewed long-term video electroencephalographic (EEG) monitoring to confirm the diagnosis. Patients’ demographic information was extracted from medical records or direct interviews based on clinical characteristics and history taking. Results: Among 1530 patients admitted during the study period, 12 out of 17 previously diagnosed patients confirmed their diagnosis. Among the group of confirmed patients, seven were boys and five were girls. The average age of seizure onset was 3.4±1.7 years. Except for absence seizures, five out of 12 had no other types of seizures. Two patients showed generalized tonic-clonic events as associated seizures. One patient had astatic seizures, in the form of head drop, one patient had myoclonic seizures, and three patients had focal seizures without persistency in the EEG. Eleven of the 12 patients had focal electrographic findings during recording, with eight having focal epileptiform discharges during the interictal period. Conclusion: JS is an under-recognized epileptic syndrome requiring accurate diagnosis through identifying seizure types and EEG features. Although it is classified as a generalized epilepsy, focal seizures have been reported in a few case reports and were observed in three patients during the ictal period in our study. Additionally, focal electrographic findings were prevalent during the interictal period. Further research is needed to better understand the clinical and neurophysiological aspects of this syndrome